2017
DOI: 10.1016/j.eats.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Joint Preservation Surgery for Medial Compartment Osteoarthritis

Abstract: Single compartment osteoarthritis is a commonly encountered condition in the middle-aged population, with the medial compartment being the most commonly involved compartment. Medial compartment osteoarthritis becomes seriously disabling for these active patients, with a very few definitive solutions. These patients quickly stop responding to the conservative methods such as lifestyle modification, drugs, physiotherapy, and rehab programs. Less invasive procedures such as intra-articular injections or joint deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…34 Although no clinical association can be drawn between our findings and future degenerative changes, it is interesting to acknowledge the articular cartilage on the posterior aspect of the medial condyle was found to be the most affected area in advanced osteoarthritic knees. 35 Our findings are also consistent with a previous study by Goyal et al, 36 who showed that on the tibial surface, the medial, or posteromedial half of the medial tibial plateau, are the most common areas to suffer chondral damage.…”
Section: Discussionsupporting
confidence: 92%
“…34 Although no clinical association can be drawn between our findings and future degenerative changes, it is interesting to acknowledge the articular cartilage on the posterior aspect of the medial condyle was found to be the most affected area in advanced osteoarthritic knees. 35 Our findings are also consistent with a previous study by Goyal et al, 36 who showed that on the tibial surface, the medial, or posteromedial half of the medial tibial plateau, are the most common areas to suffer chondral damage.…”
Section: Discussionsupporting
confidence: 92%
“…The barrel vault osteotomy was subsequently published in 1976 by Maquet 5 (Fig 1A). More recently, opening wedge 6 and combination (opening/closing) valgus 7 tibial osteotomies have been described.
Fig 1(A) Diagram of the Maquet barrel vault osteotomy with pins, left knee, premanipulation. (B) Diagram of the Maquet barrel vault osteotomy with parallel pins, left knee, postmanipulation.
…”
mentioning
confidence: 99%